Clustered architecture of ipsilateral and interhemispheric connections in macaque ventrolateral prefrontal cortex - Hu, Danling; Li, Hangqi; Takahata, Toru; Tanigawa, Hisashi (Frontiers in Neural Circuits, 2025)
The fine-scale organization of intrinsic and extrinsic connections in the primate ventrolateral prefrontal cortex (VLPFC), a region essential for higher cognitive functions, remains poorly understood. This contrasts with, for example, the well-documented stripe-like intrinsic circuits of the dorsolateral prefrontal cortex (DLPFC). To elucidate the circuit architecture supporting VLPFC function, we investigated the spatial organization of connections targeting the caudal VLPFC (primarily area 45A) in macaque monkeys using multiple retrograde tracers. Analyzing the distribution of labeled neurons in flattened tangential sections revealed that laterally projecting connections within the same hemisphere formed distinct clusters, not only in the VLPFC but also in the DLPFC. These clusters often spanned multiple cortical layers, suggesting a columnar-like organization. The width (minor axis) of these clusters was approximately 1.2 mm. Similarly, contralateral callosal projection neurons were also arranged in clusters. Additionally, inputs originating from the superior temporal sulcus were found to arise from discrete clusters of neurons. Our findings demonstrate that both long-range ipsilateral and interhemispheric connections of the caudal VLPFC share a common, fine-scale clustered architecture. This study provides an anatomical framework for understanding the structural basis of information processing and interhemispheric coordination within this critical association cortex, suggesting that this architecture is fundamental to VLPFC’s role in complex cognitive functions.